2016
DOI: 10.1128/aac.01956-15
|View full text |Cite
|
Sign up to set email alerts
|

Defining Clinical Exposures of Cefepime for Gram-Negative Bloodstream Infections That Are Associated with Improved Survival

Abstract: iThe percentage of time that free drug concentrations remain above the MIC (fT >MIC ) that is necessary to prevent mortality among cefepime-treated patients with Gram-negative bloodstream infections (GNBSI) is poorly defined. We conducted a retrospective study of adult patients with GNBSI. Eligible cases were frequency matched to ensure categorical representation from all MICs. Organism, MIC, infection source, gender, age, serum creatinine, weight, antibiotic history, and modified APACHE II score were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 32 publications
0
53
1
2
Order By: Relevance
“…The nonparametric adaptive grid (NPAG) algorithm (29-31) with adaptive gamma implemented within the Pmetrics package (version 1.4.0; Laboratory of Applied Pharmacokinetics and Bioinformatics, Los Angeles, CA) for R (32) was used for all PK model-fitting procedures, as previously described (33)(34)(35)(36). There were 80,021 initial grid points.…”
Section: Methodsmentioning
confidence: 99%
“…The nonparametric adaptive grid (NPAG) algorithm (29-31) with adaptive gamma implemented within the Pmetrics package (version 1.4.0; Laboratory of Applied Pharmacokinetics and Bioinformatics, Los Angeles, CA) for R (32) was used for all PK model-fitting procedures, as previously described (33)(34)(35)(36). There were 80,021 initial grid points.…”
Section: Methodsmentioning
confidence: 99%
“…The parameter estimations we provided allow the practicing clinician to use population modeling to improve the chance that the patient will receive the most optimal therapy. It has been suggested that 100% f T>MIC should be a therapeutic goal in patients who are neutropenic . Among patients with neutropenic fever treated with cefepime, these targets appear possible if the pathogen MIC is 4 mg/L or less.…”
Section: Discussionmentioning
confidence: 99%
“…The log‐likelihood ratio test was used to compare competing models, and p<0.05 was required for increased complexity with agreement from the Aikaike Information Criteria (AIC). Cefepime was previously shown to fit one‐ and two‐compartment PK models well . Simple one‐compartment models parameterized with elimination rate constants are regularly used in traditional PK modeling and do not require the aid of advanced computer modeling software.…”
Section: Methodsmentioning
confidence: 99%
“…41,146-152 For these agents, a broad range of f T >MIC values from >45-100% have been reported as necessary for achievement of favorable clinical or microbiological outcomes, a likely consequence of heterogeneous patient populations, infecting organisms, and study designs. However, the most robust evidence remains in line with in vitro and animal estimates, with cefepime f T >MIC values of >53-74% being associated with up to a 10-fold higher likelihood of favorable outcome.…”
Section: Antimicrobial Pharmacodynamicsmentioning
confidence: 99%
“…However, the most robust evidence remains in line with in vitro and animal estimates, with cefepime f T >MIC values of >53-74% being associated with up to a 10-fold higher likelihood of favorable outcome. 149,151,152 Indeed, in a large study assessing the adequacy of contemporary beta-lactam dosing regimens in critically ill patients, the inability to attain a f T >MIC >50% was associated with a 32% decreased likelihood of a positive clinical outcome. 41 Extended infusion regimens of certain beta-lactams have become a widespread means of maximizing f T >MIC in specific clinical scenarios.…”
Section: Antimicrobial Pharmacodynamicsmentioning
confidence: 99%